2009
DOI: 10.1093/jleo/ewp018
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of "Crying Wolf" : The Economics of Money Laundering Enforcement

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.The paper shows how excessive reporting, called "crying wolf", can dilute the information value of reports. Excessive reporting is investigated by undertaking the first formal analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 15 publications
2
65
0
1
Order By: Relevance
“…This means that more reports should be seen as a positive contribution to combating laundering. But as Takats [28] warned, more reports could just mean that the private sector, afraid of being fined, starts reporting more and more thus diluting information rather than providing additional insight to the authorities. Unger and van Waarden [38] showed that it is even not clear whether more or less reporting indicated an improvement of anti-money laundering policy.…”
Section: Money Launderingmentioning
confidence: 99%
“…This means that more reports should be seen as a positive contribution to combating laundering. But as Takats [28] warned, more reports could just mean that the private sector, afraid of being fined, starts reporting more and more thus diluting information rather than providing additional insight to the authorities. Unger and van Waarden [38] showed that it is even not clear whether more or less reporting indicated an improvement of anti-money laundering policy.…”
Section: Money Launderingmentioning
confidence: 99%
“…The model shows that harmful excessive reporting, known as -crying wolf,‖ remains a possibility. As banks cannot share its signal with the government, the government must decide on reports proffered by the banks (Takáts, 2007).…”
Section: Crying Wolf Theorymentioning
confidence: 99%
“…Even regulators acknowledged it had proved costly to implement (FSA, 2003) and it was simple for money launderers to manipulate the system to their advantage by, for example, depositing sums just below the threshold to avoid triggering a suspicious transaction report (Takats, 2011). However, more damning, was that it encouraged banks to do just enough to satisfy the requirement of the law by following what has been labelled as a 'tick-box' approach to compliance (Harvey & Lau, 2009;Killick & Parody, 2007).…”
Section: Historical Context a Rule Based Approachmentioning
confidence: 99%
“…Several scholars have examined the problems arising from the risk-based approach (Anna, 2011;Demetis & Angell, 2007) with a number examining through application of game theory (Araujo, 2010;Arnone & Borlini, 2010); or agency theory (Araujo, 2008;Masciandaro, 1999Masciandaro, , 2005Masciandaro & Filotto, 2001;Pellegrina & Masciandaro, 2009;Takats, 2011) the conditions under which the approach would be effective. We follow a different line of reasoning arguing that the risk-based approach is proving to be difficult to implement because the traditional theories of risk are not easily transferable to the arena of AML.…”
Section: Introductionmentioning
confidence: 99%